Structural diversity in manganese, iron and cobalt complexes of the ditopic 1,2- bis(2,2’-bipyridyl-6-yl)ethyne ligand and observation of epoxidation and catalase activity of manganese compounds - Madhu, Vedichi; Ekambaram, Balaraman; Shimon, Linda J. W.; Diskin, Yael; Leitus, Gregory; Neumann, Ronny (Royal Society of Chemistry, 2010)
A ditopic 1,2-bis(2,2′-bipyridyl-6-yl)ethyne ligand, L, has been synthesized for the first time by consecutive Suzuki and Sonogashira coupling reactions either in a one- or two-step synthesis. Coordination of L with some first-row transition metals, Fe, Mn and Co showed a very rich structural diversity that can be obtained with this ligand. Reaction of L with MnII(OAc)2 yielded a dimanganese(II) complex, [Mn2L(μ-OAc)3]PF6, (1) where the two somewhat inequivalent trigonal-bipyramidal Mn atoms separated by 3.381 Å are bridged by L and three acetate moieties. A similar reaction of L with MnIII(OAc)3 yielded a very different dimanganese complex [Mn2L′(OH)(OAc)2(DMF)2]PF6·DMF (2) where L′ is a E-1,2-bis(2,2′-bipyridyl-6-yl)ethene fragment that was formed in situ. The L′ ligand bridges between the two Mn centers, despite its trans configuration, which leads to a very strained ethene bridging moiety. The Mn atoms are also bridged by two acetate ligands and a hydroxy group that bridges between the Mn atoms and the ethene fragment; DMF completes the octahedral coordination around each Mn atom which are separated by 3.351 Å. A comproportionation reaction of L with MnII(OAc)2 and n-Bu4NMnO4 yielded a tetramanganese compound, [Mn4(μ3-O)2(OAc)4(H2O)2L2](PF6)2·2CH3CN (3). Compound 3 has a dimer of dimers structure of the tetranuclear Mn core that consists of binuclear [Mn2O(OAc)2L]+ fragment and a PF6 anion. BVS calculations indicate that 3 is a mixed-valent 2MnII plus 2MnIII compound where two [MnII2O(OAc)2L]+ fragments are held together by MnIII–O inter-fragment linkers which have a distorted octahedral geometry. The Mn atoms in the [Mn2O(OAc)2L]+ fragments have a capped square-pyramid configuration where an aqua ligand is capped on one of the faces. Although the aqua ligand is well within a bonding distance to a carbon atom of the proximal ethyne bridge, there does not appear to be an oxygen–carbon bond formation, rather the ligand is constrained in this position, as deduced by the observation that the bond lengths and angles of the ligand are essentially the same as those for the free ligand, L. Reaction of L with perchlorate or triflate salts of Fe(II), Mn(II) and Co(II) in dry acetonitrile yielded binuclear triple helicate structures (2[thin space (1/6-em)]:[thin space (1/6-em)]3 metal to L ratios) [Fe2L3](CF3SO3)4·CH3CN (4), [Mn2L3](ClO4)4·1.7CH3CN·1.65EtOEt (5) and [Co2L3](ClO4)4·2CH3CN·2EtOEt (6) where each M(II) center with a slightly distorted octahedral geometry is bridged by three of the ditopic ligands. The M–M distances varied; 5.961 Å (Mn), 6.233 Å (Co) 6.331 Å (Fe). Reaction of L with Co(ClO4)2·6H2O in wet acetonitrile yielded a dicobalto(III) compound, [Co2L′3(O)2](ClO4)2·H2O (7), with two types of L′ fragments; one bridging between the two Co centers and two non-bridging ligands, each bonded to a Co atom via one bipyridyl group where the other is non-bonding. The octahedral coordination sphere around each Co atom is completed by the formation of a cobalt–carbon bond from the two carbon atoms of the ethene moiety of the bridging ligand and by a hydroxy moiety that is also bonded to the ethene group of the non-bridging ligand. Reaction of L with Co(ClO4)2·6H2O in dry acetonitrile in the presence of Et3N yielded the tetracobalto(II) complex {[Co2L4(OH)4](ClO4)4}2 (8) with a unique twisted square configuration of cobalt ions with Co–Co distances of 3.938 to 4.131 Å. In addition to the L bridging ligand the Co atoms are linked by hydroxy moieties. Some preliminary catalytic studies showed that the Mn compounds 1 and 2 were active (high yield within 3 min) for alkene epoxidation with peracetic acid and hydrogen peroxide dismutation (catalase activity).